Representasi Taman Baluran sebagai Inspirasi Batik Painting dalam Menyampaikan Nilai Alam dan Budaya Lokal - Dhea Ananda Rahmatullah; Swastika Dhesti Anggriani (Jurnal Pendidikan dan Kebudayaan (JURDIKBUD), 2025)
Baluran Park is a conservation area with 26 species of animals, 444 species of plants and 155 species of birds in Baluran Park. This study aims to create a work of batik motifs in Baluran Park through batik painting artwork that can introduce Baluran Park tourist attractions to the public, and also as a form of promotion through the media of batik painting or painting. The purpose of this study is to describe and explain the process of exploration, improvisation process, and the results of batik painting works inspired by Baluran Park. This research method uses the creation method according to Alma Hawkins. The results of this creation are that at the exploration stage, ideas were found, namely fauna which were used as ideas for creation, and also the use of eco print techniques using teak leaves and natural dyes from turmeric and secang. At the improvisation stage, eight sketches were produced consisting of sketches of deer, bulls, leopards, mangrove cats, and peacocks. At the formation stage, the eight sketches that went through the creation process became eight batik paintings that will be exhibited. The eight works are titled: Psyche, Diversiteit Van Baluran, Fortitudo, Dewi Pelindung, Kecantikan Langka, Kuat Perlindungan, Panthera Herten, Baluran Kaart. The creation of this painted batik is to remind the public of the importance of maintaining and protecting the existing biodiversity so that it does not become extinct.